Dynamics of the chemical composition and productivity of composts for the cultivation of Agaricus bisporus strains - Andrade, Meire Cristina Nogueira de [UNESP]; Jesus, João Paulo Furlan De [UNESP]; Vieira, Fabrício Rocha [UNESP]; Viana, Sthefany Rodrigues Fernandes [UNESP]; Spoto, Marta Helena Fillet; Minhoni, Marli Teixeira De Almeida [UNESP] (Sociedade Brasileira de Microbiologia, 2013)
Two compost formulations based on oat straw (Avena sativa) and brachiaria (Brachiaria sp.) were tested for the cultivation of three Agaricus bisporus strains (ABI-07/06, ABI-05/03, and PB-1). The experimental design was a 2 x 3 factorial scheme (composts x strains) with 6 treatments and 8 repetitions (boxes containing 12 kg of compost). The chemical characterization of the compost (humidity, organic matter, carbon, nitrogen, pH, raw protein, ethereal extract, fibers, ash, cellulose, hemicellulose, and lignin) before and after the cultivation of A. bisporus and the production (basidiomata mass, productivity, and biological efficiency) were evaluated. Data were submitted to variance analysis, and averages were compared by means of the Tukey's test. According to the results obtained, the chemical and production characteristics showed that the best performances for the cultivation of A. bisporus were presented by the compost based on oat and the strain ABI-07/06.
Keywords: Agaricus bisporus; productivity; strains; compost; nutritional value